USING MAGIC BOTTLE TO IMPROVE STUDENTS’ SPEAKING SKILLS - Ling Jen, Shirley (jfpublisher, 2023)
Speaking has been the main problem for majority of Malaysian students as they are afraid to make mistakes. In order for students to be understood while speaking in English, they need to be able to pronounce English words clearly. To solve this problem, a game ‘Magic Bottle’ was developed in this study. This research was conducted on a group of 27 students from Sekolah Menengah Kebangsaan Taman Universiti, Skudai, Johor Bahru. It was triangulated through analysis of PBD Assessment Reports, a set of pre-test and post-test, participant observation and interview. Early observation shows that none of the students passed their PBD Speaking Skills Assessment. Only 2 out of 27 students (7%) scored Band 2 in their PBD Assessment (Pelaporan Pentaksiran Bilik Darjah) for Speaking Skills. The rest, 25 out of 27 students (93%) only scored Band 1 in their Speaking Assessment. All the students failed in the first PBD Speaking Skills Assessment. In this study, students were taught about pronunciation using 'Magic Bottle'. In the game, students were exposed to the correct pronunciation of the difficult words. They were asked to read and role play the sentences in the game. The research showed that students had improved their pronunciation through ‘Magic Bottle’. The T-Test conducted at the end of the test shows that there was a significant improvement between the students’ post-test and pre-test results. Students had also shown improvement in their PBD Speaking Skills.